TATA, DURASI, DAN FREKUENSI DALAM NOVEL ORANG-ORANG PROYEK KARYA AHMAD TOHARI: (Analisis Struktur Naratif) - hartono, Hartono (LITERA, 2005)
This research study employs the theory of narrative structure by SeymourChatman. The study aims to describe plot elements comprising kernel and satellite,arrangement, duration, and frequency available in Orang-orang Proyek, a novel byAhmad Tohari.The subject of the study was Orang-orang Proyek (2002, the first impression), anovel by Ahmad Tohari, and the focuses were plot elements covering kernel andsatellite, arrangement, duration, and frequency. The data were collected throughreading and recording. The novel was read and reread and its discourse andsentential and sub-sentential units containing narrative elements were recorded.The data were analyzed using the descriptive qualitative technique.The research findings show that Orang-orang Proyek contains 44 kernels and132 satellites. On the basis of its logical order, it reveals that causality order can beparallel with temporal order. Chronologically, the beginning of the story also results,though not directly, in subsequent events. From the relation between the past and thepresent, the novel shows a tendency that the analeptic occurring before the presentwas almost the same as that occurring after the present. The novel contains 20 externalanachronisms, 18 mixed anachronisms, and 13 internal anachronisms. The durationincludes, from the most to the least, scene, summary, distraction, pause, and ellipsis.The dominance of scene, followed by summary, shows that the narrator’s role in thestory is very small; most parts of the story are expressed through dialogues amongcharacters to make it more interesting. Singular events dominate frequency in thenovel, followed by iterative frequency, multiple-singular frequency, and repetitivefrequency. Dominant singular events make the novel more lively and interesting.Key words: narrative structure, arrangement, duration, and frequency